2021
DOI: 10.1371/journal.pone.0256708
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin inhibition causes context-dependent cell death of leukemia and lymphoma cells

Abstract: Current chemotherapy for treatment of pediatric acute leukemia, although generally successful, is still a matter of concern due to treatment resistance, relapses and life-long side effects for a subset of patients. Inhibition of dynamin, a GTPase involved in clathrin-mediated endocytosis and regulation of the cell cycle, has been proposed as a potential anti-cancer regimen, but the effects of dynamin inhibition on leukemia cells has not been extensively addressed. Here we adopted single cell and whole-populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Acute Lymphoblastic Leukemia (ALL) stands out as the most commonly diagnosed cancer in children, characterized by an aggressive growth of immature lymphocytes [10] . This disease accounts for 80% of all pediatric leukemias and 25% of all childhood cancers, making it the leading type of pediatric cancer [11] . In ALL, there is a marked increase in the production of blastocysts, immature cells in the bone marrow and blood.…”
Section: Acute Lymphoblastic Leukemia In Pediatricsmentioning
confidence: 99%
“…Acute Lymphoblastic Leukemia (ALL) stands out as the most commonly diagnosed cancer in children, characterized by an aggressive growth of immature lymphocytes [10] . This disease accounts for 80% of all pediatric leukemias and 25% of all childhood cancers, making it the leading type of pediatric cancer [11] . In ALL, there is a marked increase in the production of blastocysts, immature cells in the bone marrow and blood.…”
Section: Acute Lymphoblastic Leukemia In Pediatricsmentioning
confidence: 99%
“…33 Dynamin inhibition by Dyngo®-4a and MiTMAB causes death of leukemia and lymphoma cancer cells. 34 We have demonstrated that clinically used antipsychotic medications in the phenothiazine class, including the archetypical inhibitor chlorpromazine, are dynamin inhibitors. 35 In a human study the phenothiazine prochlorperazine reduces endocytosis in humans demonstrating that endocytosis inhibitor therapy is not inherently unsafe.…”
Section: Introductionmentioning
confidence: 99%
“… [27] In addition, dynamin inhibitors alter cell signalling pathways and have been shown to enhance the effects of existing chemotherapeutic approaches. [ 49 , 50 ] This suggests that targeting dynamin may be a novel anti‐cancer strategy. In support of this, dynole‐34‐2 and a phenothiazine drug were recently shown to be effective as combination therapies in mouse models of leukemia and head and neck cancer respectively,[ 49 , 51 ] or as a mono‐therapy in glioblastoma.…”
Section: Introductionmentioning
confidence: 99%